2016
DOI: 10.1002/chem.201600189
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Carbon Dioxide on Unsaturated Metal Sites in M2(dobpdc) Frameworks with Exceptional Structural Stability and Relation between Lewis Acidity and Adsorption Enthalpy

Abstract: A series of metal-organic frameworks (MOFs) M2 (dobpdc) (M=Mn, Co, Ni, Zn; H4 dobpdc=4,4'-dihydroxy-1,1'-biphenyl-3,3'-dicarboxylic acid), with a highly dense arrangement of open metal sites along hexagonal channels were prepared by microwave-assisted or simple solvothermal reactions. The activated materials were structurally expanded when guest molecules including CO2 were introduced into the pores. The Lewis acidity of the open metal sites varied in the order MnZn, as confirmed by C=O stretching bands… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 47 publications
(58 reference statements)
3
28
0
Order By: Relevance
“…The activation energy of the desorption process was roughly estimated to be 159.0 kJ mol −1 for M=Mg, 146.7 kJ mol −1 for M=Mn, 153.8 kJ mol −1 for M=Co, and 168.6 kJ mol −1 for M=Ni. The NH 3 desorption temperature and activation energy trend was as follows: Ni > Mg > Co > Mn, which closely resembles the CO 2 adsorption enthalpy trend observed in the M 2 (dobpdc) series [29] . Furthermore, this order directly reflects the Lewis acidity strength of the metal ions of these systems.…”
Section: Resultssupporting
confidence: 68%
“…The activation energy of the desorption process was roughly estimated to be 159.0 kJ mol −1 for M=Mg, 146.7 kJ mol −1 for M=Mn, 153.8 kJ mol −1 for M=Co, and 168.6 kJ mol −1 for M=Ni. The NH 3 desorption temperature and activation energy trend was as follows: Ni > Mg > Co > Mn, which closely resembles the CO 2 adsorption enthalpy trend observed in the M 2 (dobpdc) series [29] . Furthermore, this order directly reflects the Lewis acidity strength of the metal ions of these systems.…”
Section: Resultssupporting
confidence: 68%
“…TheNH 3 uptake of the Mg and Ni compounds was observed to decrease.T his could be associated with the significant interactions between NH 3 and the metal centers,as Mg and Ni have the strongest Lewis acidities among the metal Angewandte ions in the M 2 (dobpdc) series. [29] After the cyclic adsorption test, all samples,e xcept for Zn, retained their structural integrity,asconfirmed by PXRD,IR, and N 2 sorption results (Supporting Information, Figures S16-S22, Table S4). The peaks of the Zn analog in the PXRD pattern significantly weakened after the first cycle,suggesting that the capacity loss originates from structural collapse (Supporting Information, Figures S16 and S22).…”
Section: Resultsmentioning
confidence: 66%
“…In the case of CO 2 , for example, it has been reported that the presence of unsaturated open metal sites can greatly enhance the CO 2 sorption capacity due to considerable polarizability and quadrupole moment. Open metal cations play as Lewis acidic nodes that strongly favors CO 2 [ 40 , 41 ]. The occurrence of breathing is reported to significantly affect the pore volume, and, therefore, the gas sorption ability.…”
Section: Metal Organic Framework (Mofs)mentioning
confidence: 99%